ES&T in the 21st Century: A Data-Driven Analysis of Research Topics, Interconnections, And Trends in the Past 20 Years - Zhu, Jun-Jie; Dressel, Willow; Pacion, Kelee; Ren, Zhiyong Jason (Environmental science & technology, 2021)
Environmental Science & Technology (ES&T) has served a leadership role in reporting advanced and significant research findings for decades and accumulated tremendous amount of high-quality literature. In this study, we developed tailored text mining methods and analyzed 29 188 papers published in ES&T from 2000 to 2019, and we performed data-driven analyses to reveal some critical information and guidance on what has been published, what topical changes have evolved, and what are the areas that deserve additional attention. While top research keywords remained stable (water, sorption, soil, emiss, oxid, exposur), the trending up and emerging keywords showed clear shift over the years. Keywords related to nanobased materials (nanoparticl, nanomateri, carbon nanotub), climate and energy (climat, ch4, greenhouse gas emiss, mitig, energi), and health (exposur, health, ingest) demonstrated the strongest uptrend in the past 10 years, while plastics and PFAS were among clear emerging topics in the past 5 years. Co-occurrence analysis showed distinct associations between media (water, soil, air, sediment), chemicals (pcb, humic subst, particulate matt), processes (sorption, remov, degrad), and properties (kinet, mechan, speciat). Furthermore, a rule-based classification deciphered trends, distributions, and interconnections of articles based on either monodomains (air, soil, solid waste, water, and wastewater) or multidomains. It found water and wastewater cross-discipline articles tended to have higher citation values, while air domain tended to stand alone. Water and air monodomains consistently increased their shares in publications (together 56.3% in 2019), while shares of soil studies gradually declined. This study provides new data-driven methods on literature mining and offers unique insights on environmental research landscape and opportunities.